(untitled) (Research, Society and Development, 2020)
Surgery is one of the therapeutic alternatives to solve a health problem. It is known that patients have the most diverse psycho-emotional reactions in the preoperative period. Preoperative nursing care represents the main instrument for establishing a relationship of trust between the nurse and the patient, seeking to provide a reduction in traumatic reactions and an improvement in the quality of life. The objective is to know the memories and psycho-emotional reactions of patients during the preoperative nursing consultation for total hip arthroplasty. It is a descriptive exploratory research, with a qualitative approach. Interviews were conducted with eight patients and the reports were transcribed from June to August 2019 to use the content analysis method. Two categories originated according to the patients’ reports, the first brought the reactions and bonds established between the professional nurse and the patient during the outpatient consultation and the second showed the perceptions of those advised during home visits. The patient’s responsibility for recovery and mental health care was perceived. There is a need for new research that addresses mental disorders in several areas, not only in pre-surgical environments, instigating reflections for the construction of new work practices to provide a qualified, effective and excellent service.